2009
DOI: 10.1111/j.1750-3639.2008.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Neuronal Pathology in Multiple Sclerosis

Abstract: The objective of this study was to assess neuronal pathology in the spinal cord in multiple sclerosis (MS), both within myelinated and demyelinated tissue. Autopsy material was obtained from 38 MS cases and 21 controls. Transverse sections were taken from three spinal cord levels and stained using Luxol Fast Blue/Cresyl Violet and myelin protein immunohistochemistry. Measurements of neuronal number and size were made for all neurons within the anterior horns of the gray matter. Neurons were classified as moton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 35 publications
7
70
1
1
Order By: Relevance
“…Ultra-high field MRI may also prove to be a valuable tool to assess GM damage in CNS areas other than the cortex and including the spinal cord and the cerebellum as histopathologic examinations described GM demyelination and neuronal pathology in these structures in MS. [33][34][35] …”
Section: Discussionmentioning
confidence: 99%
“…Ultra-high field MRI may also prove to be a valuable tool to assess GM damage in CNS areas other than the cortex and including the spinal cord and the cerebellum as histopathologic examinations described GM demyelination and neuronal pathology in these structures in MS. [33][34][35] …”
Section: Discussionmentioning
confidence: 99%
“…For example, several recent studies of grey and white matter demyelination in different regions of the CNS found that the extent of cortical demyelination is greater than that found in white matter 34 and that, although cortical demyelination sometimes occurred together with demyelination in the adjacent white matter (leukocortical lesions), in most instances, the cortex was affected independently from white matter lesions 35,36 . Another study observed a gradient of neuronal loss in the precentral gyrus of MS cases that exhibited extensive subpial demyelination with the greatest loss in the outer cortical layers 17 .…”
Section: Evidence For Independent Grey Matter Damagementioning
confidence: 99%
“…Schirmer et al also reported a number of phosphorylated NF-H positive neurons in anterior horn cells of MS patients and noted that they were more pronounced in early and active lesions [12]. Considering the significant depletion of spinal motor neurons in MS that has been described in previous studies [10][11][12], it is likely that in non-immunoreactive areas of spinal cord, most damaged neurons have disappeared, although some may also have recovered. This hypothesis is supported by our comparison of the motor neuron count in a lumbar subgroup of 4 MS cases.…”
mentioning
confidence: 88%
“…Axonal damage [2][3][4][5], neuronal apoptosis [6,7] and neuronal loss [8] in grey and white matter lesions have been described both in MS and its widely-used animal model, experimental autoimmune encephalomyelitis (EAE). In spinal cord, substantially reduced nerve cell counts were found both in EAE [9] and MS [10][11][12].…”
Section: Introductionmentioning
confidence: 95%